Unveiling mitochondrial transfer in tumor immune evasion: mechanisms, challenges, and clinical implications - Liu, Ruoyan; Shan, Wenhui; Wang, Zhening; Wang, Hong; Li, Chunyan; Yang, Lei; Guo, Rui (Frontiers in Immunology, 2025)
BackgroundMitochondrial transfer, the intercellular transmission of mitochondria via tunneling nanotubes(TNTs), extracellular vesicles(Evs), or cell fusion, has emerged as a critical mechanism in cancer progression. Increasing evidence suggests that this phenomenon not only supports tumor cell metabolism and drug resistance but also contributes to immune evasion, a hallmark of cancer.ObjectiveThis study aims to systematically explore the intellectual structure, research hotspots, and emerging trends of mitochondrial transfer in tumor immune evasion using bibliometric and visualization tools.MethodPublications from 2003 to 2025 were retrieved from the Web of Science Core Collection. CiteSpace and VOSviewer were used to analyze annual outputs, co-occurring keywords, citation bursts, clustering patterns, and co-cited references.ResultsA total of 124 records were analyzed. The number of publications increased sharply after 2017, indicating growing research interest. Key terms such as “tunneling nanotubes,” “mitochondrial transfer,” and “immune escape” were frequently co-mentioned. Although “immune escape” is retained here to reflect the exact terminology used in the bibliometric database (Web of Science Core Collection), the manuscript text consistently adopts the term “immune evasion” for conceptual clarity and terminological standardization. Timeline cluster analysis identified several sustained hotspots, including acute myeloid leukemia (AML), stromal cells, and the cancer microenvironment. Citation burst analysis revealed emerging attention toward “expression,” “stem cells,” and “tumor microenvironment” in recent years.ConclusionMitochondrial transfer has transitioned from a structural phenomenon to a key immunological modulator in cancer. This bibliometric analysis highlights its central role in immune evasion and identifies future research directions for therapeutic exploitation.